Pengaruh Human Relations Mahasiswa dalam Menyelesaikan Konflik di Lingkup Pertemanan - Anisa Nurbaiti; Utari Mutiara Ayu; Setya Prihatining Tyas; Bernika Meilani Ifada; April Laksana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Human relations are a fundamental aspect of human social life, including in the student sphere. This research explores the role of human relations in creating a harmonious friendship environment on campus. Using Human Relations theory, this study highlights the importance of interpersonal communication, empathy, and conflict management in improving the quality of students' social interactions. A qualitative approach through participatory observation and literature review was used to deeply understand the phenomenon. The results showed that positive relationships between students can increase security, happiness, and productivity, as well as promote intellectual and emotional development. Conversely, poorly managed conflict can have a negative impact on academic performance and mental health.